Circ_0005927 Inhibits the Progression of Colorectal Cancer by Regulating miR-942-5p/BATF2 Axis - Yu C; Li D; Yan Q; Wang Y; Yang X; Zhang S; Zhang Y; Zhang Z (Cancer Management and Research, 2021)
Chao Yu,* Deguan Li,* Qiang Yan, Yigao Wang, Xiaodong Yang, Shangxin Zhang, Yonghong Zhang, Zhen Zhang Department of General Surgery, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhen ZhangDepartment of General Surgery, The First Affiliated Hospital of Anhui Medical University, No. 218, Jixi Road, Shushan District, Hefei, Anhui, 230022, People’s Republic of ChinaTel +86-055162923887Email zlkgep@163.comBackground: Colorectal cancer (CRC) is one of the most common aggressive neoplasms worldwide. Circular RNAs (circRNAs) have been involved in the biological process of CRC. This study aimed to explore the effects of circ_0005927 on CRC progression and underneath mechanism.Materials and Methods: The expression of circ_0005927, microRNA-942-5p (miR-942-5p) and basic leucine zipper ATF-like transcription factor 2 (BATF2) was detected by quantitative real time polymerase chain reaction (qRT-PCR). The protein expression of BATF2 was determined by Western blot. The effects among circ_0005927, miR-942-5p and BATF2 on cell colony-forming ability, apoptosis and migratory and invasive abilities were revealed by cell colony formation, flow apoptosis and transwell assays, respectively. The associated relationship between miR-942-5p and circ_0005927 or BATF2 was predicted by Circinteractome or TargetScan online database, and identified by dual-luciferase reporter or RNA immunoprecipitation (RIP) assay. The impacts of circ_0005927 overexpression on tumor growth in vivo were investigated by in vivo tumor formation assay.Results: Circ_0005927 expression and the mRNA and protein expression of BATF2 were dramatically downregulated, while miR-942-5p expression was obviously upregulated in CRC tissues or cells compared with control groups. Circ_0005927 overexpression repressed cell colony-forming ability, migration and invasion, whereas induced cell apoptosis in CRC; however, these impacts were hindered by miR-942-5p mimic or BATF2 knockdown. Furthermore, circ_0005927 was a sponge of miR-942-5p, and miR-942-5p bound to BATF2. In addition, circ_0005927 overexpression repressed tumor growth in vivo.Conclusion: Circ_0005927 suppressed cell colony-forming ability, migration and invasion, and promoted cell apoptosis by sponging miR-942-5p to induce BATF2 in CRC. The possible mechanism provides a theoretical basis for the study of circRNA-directed therapy for CRC.Keywords: circular RNA, circ_0005927, miR-942-5p, BATF2, CRC